The relationship of teacher-student interpersonal behaviour with student sex, cultural background and student outcomes. - Rickards, Anthony W.J. (Curtin University, 1998)
The major purposes of this study were to provide validation data for the Questionnaire on Teacher Interaction (QTI) with a large Australian sample and examine the relationship of teacher-student interpersonal behaviour with student sex, cultural background and student outcomes. The sample from lower secondary science classrooms in Australia consisted of 3,215 students in 158 classes in 43 schools in two Australian states, namely Tasmania and Western Australia. The sample was chosen carefully so as to be representative, though only co-educational classes were used in order to permit an unconfounded test of sex differences. Students and teachers completed a questionnaire which included the QT1, an attitude to class scale based on the Test of Science Related Attitudes (TOSRA), a cognitive achievement measure based on items from the Test of Enquiry Skills (TOES) and a five-item cultural background survey. The study follows the current trend in the field of classroom environment research of combining qualitative and quantitative methods. The qualitative component of the study involved about 100 interviews. This study is unique in that it provides a very large database of teacher-student interaction data in science classrooms and provides new insights into the relationships between teacher-student interpersonal behaviour with student sex, cultural background and student outcomes. The study found that there were associations between teacher student interpersonal behaviour and student sex and that there were differences in the way that students from different cultural backgrounds perceived their learning environments. Student achievement and student attitude to class were also found to be positively associated with teacher-student interpersonal behaviour. As a practical outcome of this study, the 48-item QT1 has been shown to be useful to Australian lower secondary science teachers as an initiator of self reflection on teaching practice.